Seizure as a Presentation of Permanent Neonatal Diabetes Mellitus due to Mutation in KCNJ11 Gene: A Case Report - Patnaik, Sibabratta; Sahoo, Bandya; Jain, Mukesh Kumar; Mishra, Reshmi; Behera, Jyotiranjan (Journal of Nepal Paediatric Society, 2020)
Diabetes Mellitus in first six months of life is usually monogenic and is referred to as neonatal diabetes mellitus. The incidence of neonatal diabetes is extremely rare and varies from 1:89000 to 1:400000 live births. We report a two months old baby presenting with repeated seizures; on evaluation found to have diabetic ketoacidosis and initially managed with IV insulin infusion. Genetic study revealed heterozygous mutation, p. Valin 252 Leu in KCNJ 11 gene. This mutation suggests responsiveness to oral glibenclamide. The baby has responded to therapy. Seizure as a presenting feature for hyperglycemia is a rare entity